The rationing of nursing care phenomenon in the light of scientific reports - personnel shortages, system requirements, consequences - PART II - Dorota Milecka; Henryka Homętowska; Stanisław Manulik (Kazimierz Wielki University, 2023)
Rationing of nursing care is a widespread and growing phenomenon whose causes are multifaceted and whose consequences are serious. Nursing rationing is defined as withholding or failing to perform necessary nursing tasks due to insufficient time, staffing, and/or inadequate skills. Nursing rationing is also defined as omission, delay, failure to complete, which qualifies as an error of omission. Unfinished nursing care has many negative consequences for patients, nurses and organizations. The presented series of three papers aims to show many important aspects related to rationing of care. This second part of the series of rationing of nursing care phenomenon will address the nursing shortages and demand for nursing care, nursing staffing rates and government policy, the effects of inadequate nursing care on patients and nursing staff, and the economic and social effects of inadequate nursing care.